Method of estimating initial rotor position for IPMSMs using subdivided voltage vectors based on inductance variation - Cho, Dae Hyun; Bak, Yeongsu; Lee, Kyo Beum (Journal of Power Electronics, 2020)
This paper proposes a method for estimating the initial rotor position for an interior permanent-magnet synchronous motor (IPMSM) using subdivided voltage vectors based on inductance variation. Since the stator inductance of an IPMSM varies depending on the rotor position, the current that flows through the entire IPMSM drive system can be different depending on the rotor position when a voltage vector is applied to the stator winding of the IPMSM. Therefore, the rotor position can be estimated using the differences in the currents. In the conventional method, which uses six voltage vectors to estimate the initial rotor position, the estimated position error is increased in specific regions where the phase angle of the applied voltage vector is remarkably different from that of the N pole of the rotor. This paper presents an advanced method using subdivided voltage vectors to estimate the initial rotor position more precisely in a specific region. The effectiveness of the advanced estimation method is verified by simulation and experimental results.
Keywords: Applied voltages; Conventional methods; Estimated position error; Estimation methods; Inductance variation; Initial rotor position; Interior permanent magnet synchronous motor; Voltage vectors; Inductance variation; Initial rotor position; Interior permanent-magnet synchronous motor; Subdivided voltage vectors